Analisis Pengaruh Disiplin Kerja, Kompensasi dan Budaya Organisasi terhadap Kepuasan Kerja dengan Motivasi Sebagai Variabel Moderasi: (Analysis of the Influence of Work Discipline, Compensation and Organization Culture on the Job Satisfaction With Motivation as a Moderation Variable) - Ahmad Daroji (e-Journal Ekonomi Bisnis dan Akuntansi, 2023)
The purpose of this research is to analyze the effect of work discipline, compensation, and organizational culture on job satisfaction with motivation as a moderating variable. The population in this study were all employees at the Bantul Regency Population and Civil Registration Office with ASN status, using a saturated or census sampling technique, namely determining the total sample of all members of the population, which could be as many as 40 people. Data collection was carried out using a questionnaire, which was distributed to employees of the Bantul Regency Population and Civil Registration Office with ASN status. Hypothesis testing uses the Paired Least Square (PLS) analysis tool with Smart PLS Version 3.2.9 software. The findings revealed that work discipline and organizational culture had a significant effect on job satisfaction, but compensation had no effect. In addition, motivation could not moderate the relationship between work discipline, compensation, and organizational culture and job satisfaction among Population and Registration Office employees in Bantul Regency. For further research, it is hoped that it can expand its research by considering other variables outside of this study that affect employee job satisfaction.